Procrastination, Negative Emotional Symptoms, and Mental Well-Being among college students in Saudi Arabia - Dardara, Elsaeed; Al-Makhalid, Khalid A. (Anales de Psicología / Annals of Psychology, 2022)
The main aim of the current study was the examines the relationship between procrastination, Negative Emotions, and mental well-being. Participants from Saudi Arabia (n = 886; females 344, 38.8% and 542 males, 61.2%; Mage = 24.33, SD = 5.68). Participants completed online questionnaires on the Irrational Procrastination Scale (IPS), the Depression Anxiety Stress Scales (DASS-21), and the Mental Health Continuum-Short Form (MHC-SF). As hypothesized, males procrastinated more than females. Furthermore, single ones procrastinated more than married ones. Depending on the study assumption that procrastination and negative emotional symptoms are related to poorer mental well-being, procrastination is related to higher levels of DASS-21 and decreased well-being. These findings suggest that age, gender, depression, stress, anxiety, and Well-being were predictive of procrastination. Findings add to the psychological literature and improve a better comprehension of the complicated associations between Procrastination, Negative Emotions, and Well-Being.